(untitled) (Ustozlar uchun, 2026)
Hepatocellular insufficiency in obstructive jaundice significantly worsens the prognosis and increases the risk of adverse outcomes. Since the severity of hepatic dysfunction correlates with the degree of immunological impairment, optimizing post-operative immunocorrection remains a critical issue. Aim: To investigate the state of non-specific reactivity following biliary decompression in an experimental model of obstructive jaundice in mini-pigs and to evaluate the effect of an immunomodulatory drug during the post-decompression period.